“A gente não quer só comida”: processos educativos, crianças catadoras e sociedade de consumidores - Bocasanta, Daiane Martins (Universidade do Vale do Rio do Sinos, 2009)
This Master Dissertation presents a research that has the aim to analyze the meanings assigned to the gathering of solid recycled waste – catação –, by a group of children, students from the second grade of a municipal school (situated in Santa Marta Neighborhood) at São Leopoldo, RS, who was involved in this activity, examining the language games which constitutes it. The research data was composed of interviews made with eight children with the average age of six to eleven years old, unleashed by drawings that have been done previously; observation notes and words registered in a field diary; drawings and panels made by the students and information generated from a visit to the Sanitary Landfill. The investigation was based on theoretical tools provided by different authors’ thoughts. Among them, assumed a privileged position notions coming from Michel Foucault’s theorizations – such as power, resistance, discourse and enunciation; of Ludwig Wittgenstein’s ideas of his book Philosophical Investigations
Keywords: catação de resíduos sólidos recicláveis; crianças catadoras; educação de crianças; sociedade de consumidores; children education; gathering children; gathering of recycled solid waste; consumers society; Ciências Humanas